New Jurassic Play Concepts in the Mesopotamian Basin and the Western Desert of Iraq - Al Ahmed, Ahmed Asker Najaf (Al-Nahrain Journal of Science, 2012)
Intensive tectonic activity during Zagros Orogeny (Late Cretaceous-Late Tertiary) and the final uplift in Holocene, reactivated folds and faults and eroded parts of the Lower Cretaceous, Jurassic and earlier sequences in western Iraq. Subsequently, within the Study area, the post Jurassic tectonics and the Upper Jurassic paleo-depositional environments left potential carbonate reservoirs at the basin margin (the Najmah Formation) and a potential evaporite cap rock (the Gotnia Formation) basin wards. Such relationship sealed the generated hydrocarbons from the source rocks formations (the Sargelu Formation) but it unlikely sealed the laterally migrated oil into the Najmah Formation. The major N-S fault planes of the Khleisia uplift that extended from northwestern part of Iraq to the southwestern Desert forming a barrier to laterally migrated oil and putting an end to the potential migration pathways from the Basinal Sargelu Formation in ENE Iraq. At the same time the prolonged thermal activity may have convert the organic matters within Paleozoic layers to Thermogenic gases.Total petroleum system enabled us to better understand the provenance of oil accumulated in the Najmah Formation’s layers another rock packages. According to 1-dimention model the migrated oil can pass through the Khleisia fault planes into the Middle Jurassic Muhaiwir Carbonate Formation (marginal equivalent to basinal Sargelu Formation) to form potential oil reservoir sealed by Gotnia evaporates and Kimmeridgian anhydrite .The equivalent formations located in western desert (Ubaid, Hussiniyat and Amij) Formations to the formations located in the central part (Mesopotamian Basin) which is (Butmah, Adaya, Mus and Alan Anhydrite) may consider as a new Jurassic reservoirs. So far no oil wells yet are available to cover the study of the whole area.